051. Incarcerated Umbilical Hernia in A 45-Year-Old Male with Chronic Kidney Disease: A Case Report - Harahap, Kevin Imansyah (JBN (Jurnal Bedah Nasional), 2024)
Background : Umbilical hernias are common, but incarceration can lead to serious complications, particularly in patients with comorbidities. We present a case of an incarcerated umbilical hernia in a male patient with a history of chronic kidney disease (CKD) on hemodialysis, which required emergency surgical intervention. Case: A 45-year-old male presented with intermittent umbilical pain and a lump, which appeared during straining or coughing and spontaneously reduced upon rest. The patient also experienced nausea, absence of defecation for 3 days, and absent flatus for 1 day. There was no vomiting, but a history of chronic cough and CKD was noted. On physical examination, an umbilical lump measuring 4x3x2 cm was identified. Bloodwork revealed elevated creatinine levels (6.0 mg/dL), consistent with CKD. Imaging confirmed the diagnosis of an incarcerated paraumbilical hernia, and the patient underwent emergency herniorrhaphy. Post-operative recovery was uneventful. Conclusion: This case highlights the importance of timely intervention in patients with incarcerated umbilical hernias, especially in the presence of comorbid conditions such as CKD. Emergency herniorrhaphy remains the definitive treatment for preventing life-threatening complications.